Influence of sunflower lecinn on quality indicators of wheat bread - Shevchenko, Anastasiia (My University, 2023)
Lecithin participates in almost all biochemical processes of the human body, in the formation of cell membrane structures. It is advisable to use sunflower lecithin, because it helps to lower cholesterol, improves digestion and contains a high percentage of phosphatidylcholine, which is recommended for use in diseases of the gastrointestinal tract. According to sensory indicators, the product met the standard, the addition of lecithin did not affect the color, taste and smell of the products. Porosity remains uniform, small, thin-walled. The acidity of the dough samples did not change, but the gas-forming capacity increased by 0.9%. This can be explained by the presence of choline in the composition of lecithin, which improves the fermentation capacity of yeast, which has a positive effect on the condition of yeast cells. The specific volume of bread increased by 4.5%, which correlates with increased gas formation. The dimensional stability of bread also increased by 8.9%. At the same time, the porosity of the products improved by 2.7%.
Keywords: dough; acidity; bread; sensory indicators; lecithin; кафедра технології хлібопекарських і кондитерських виробів